2006
DOI: 10.1007/s00420-006-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year follow-up study on respiratory disorders and lung function in workers exposed to organic dust from composting plants

Abstract: The exposure to organic dust at workplaces of composting facilities is associated with adverse acute and chronic respiratory health effects, including MMI, chronic bronchitis, and an accelerated decline of FVC%. The pattern of health effects differs from those at other workplaces with exposures to organic dust possibly due to high concentrations of thermo-tolerant/thermophilic actinomycetes and filamentous fungi at composting plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 22 publications
7
79
3
2
Order By: Relevance
“…The health studies have design limitations, generally involving small numbers of subjects and, in the community studies, reliant on self-reported outcomes that may be prone to bias. Further, with the exception of one cohort study that was undertaken over the course of 5 years (Bünger et al, 2007), studies were either of short time scales or cross-sectional in design, which limits interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health studies have design limitations, generally involving small numbers of subjects and, in the community studies, reliant on self-reported outcomes that may be prone to bias. Further, with the exception of one cohort study that was undertaken over the course of 5 years (Bünger et al, 2007), studies were either of short time scales or cross-sectional in design, which limits interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen occupational studies measured personal exposure of compost workers to different bioaerosol components (Bünger et al, 2007;Crook et al, 2008;Drew et al, 2007;Douwes et al, 1997;Epstein et al, 2001;Krajewski et al, 2002;Schlosser et al, 2009;Sigsgaard et al, 1994;Stagg et al, 2010;Sykes et al, 2011;Taha et al, 2007;Wheeler et al, 2001), detecting significantly high concentrations of actinomycetes, Aspergillus fumigatus, fungi, and endotoxin (Stagg et al, 2010), and elevated personal exposure levels of endotoxin in workers, particularly during composting agitation activities (Sykes et al, 2011). Four occupational studies measured mesophilic mould/fungi (Reinthaler et al, 2004;Schlosser et al, 2009;Tolvanen et al, 2005;van Kampen et al, 2014).…”
Section: Exposure Studiesmentioning
confidence: 99%
“…Occupational exposure to bioaerosols can cause various adverse health effects, such as infectious diseases, acute toxic effects, and allergies (Douwes et al, 2003;Bunger et al, 2007). Workers from specific occupational settings, such as agricultural farms and composting facilities, may be exposed to high fungal bioaerosol concentrations, resulting in increased respiratory symptoms and decreased lung functions (Bunger et al, 2007;Adhikari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, quantitative evidence on both exposure and response to bioaerosols from waste composting is limited (Pearson et al 2015) and there are few studies looking at health effects of waste composting (Giusti 2009;Pearson et al 2015;Searl, 2008;Wéry 2014). Occupational health studies of compost site workers have mainly focussed on respiratory impacts (Pearson et al 2015), with some studies showing reduction in lung function (Bunger et al 2007;Sigsgaard et al 1994); respiratory symptoms (Bünger et al 2000;Hambach et al 2012) and symptoms consistent with allergic rhinoconjunctivitis (Bünger et al 2007;Hambach et al 2012;van Kampen et al 2014); and increased chronic bronchitis (Bünger et al 2007). Community studies have reported increases in respiratory symptoms and throat and eye irritation near sites (Pearson et al 2015).…”
Section: Introductionmentioning
confidence: 99%